POLYHYDROXYALKANOATES (PHAS) PRODUCTION FROM AEROBIC-MIXED CULTURES (Malaysian Journal of Civil Engineering, 2018)
This study assessed the optimal conditions for PHA production using saponified fatty acid, derived from sunflower oil (SO). A fed-batch reactor was used to produce PHA. A mixture of sewage and semi-treated oil palm effluent from a facultative pond was cultured for six months to obtain a steady-state condition. The culture was then transferred to the fed-batch system. SO mainly contains long-chain-fatty-acid (LCFA) with unsaturated fatty acid fractions of C14:1 – C18:3, therefore the PHA production was assessed under feast-famine condition. The main purpose of supplementing saponified SO was to improve the production of PHA constituents (copolymer of hydroxyl-unit) such as hydroxybutyrates (HBs), hydroxyvalerates (HVs) and hydroxyhexanoates (HHs) in mixed cultures. Fed-batch operation under aerobic-mixed cultures increased the PHA production up to 33% of the dried cell. Although sludge submitted to aerobic condition in mixed cultures could improve the PHA production, the production rates are still low. This study found that the HBs constituent in the sludge is always higher compared to HVs and HHs. Saponified SO has high specific PHA storage rates (qp feast = 0.5 C-mol/C-mol. h) which are comparable to other vegetable oils (e.g. corn oil, soy bean oil, etc.)